Effect of Biofilm Formation by Oenococcus oeni on Malolactic Fermentation and the Release of Aromatic Compounds in Wine - Bastard, Alexandre; Coelho, Christian; Briandet, Romain; Canette, Alexis; Gougeon, Régis; Alexandre, Hervé; Guzzo, Jean; Weidmann, Stéphanie (Frontiers in Microbiology, 2016)
The winemaking process involves the alcoholic fermentation of must, often followed by malolactic fermentation. The latter, mainly carried out by the lactic acid bacterium Oenococcus oeni, is used to improve wine quality when acidity reduction is required. Moreover, it prevents microbial spoilage and improves the wine’s organoleptic profile. Prior observations showed that O. oeni is able to resist several months in harsh wine conditions when adhered on oak barrels. Since biofilm is a prevailing microbial lifestyle in natural environments, the capacity of O. oeni to form biofilms was investigated on winemaking material such as stainless steel and oak chips. Scanning Electron Microscopy and Confocal Laser Scanning Microscopy showed that O. oeni was able to adhere to these surfaces and form spatially organized microcolonies embedded in extracellular substances. To assess the competitive advantage of this mode of life in wine, the properties of biofilm and planktonic cells were compared after inoculation in a fermented must (pH 3.5 or 3.2 and 12% ethanol) The results indicated that the biofilm culture of O. oeni conferred (i) increased tolerance to wine stress, and (ii) functional performance with effective malolactic activities. Relative gene expression focusing on stress genes and genes involved in EPS synthesis was investigated in a mature biofilm and emphasized the role of the matrix in increased biofilm resistance. As oak is commonly used in wine aging, we focused on the O. oeni biofilm on this material and its contribution to the development of wine color and the release of aromatic compounds. Analytical chromatography was used to target the main oak aging compounds such as vanillin, gaiacol, eugenol, whisky-lactones and furfural. The results reveal that O. oeni biofilm developed on oak can modulate the wood-wine transfer of volatile aromatic compounds during malolactic fermentation and aging by decreasing furfural, gaiacol and eugenol in particular. This work showed that O. oeni forms biofilms consisting of stress-tolerant cells capable of efficient malolactic fermentation under winemaking conditions. Therefore surface-associated behaviors should be considered in the development of improved strategies for the control of malolactic fermentation in wine.